1999
DOI: 10.1128/aac.43.4.846
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of an Antibiotic Resistance Gene Cluster of Salmonella typhimurium DT104

Abstract: Salmonella typhimurium phage type DT104 has become an important emerging pathogen. Isolates of this phage type often possess resistance to ampicillin, chloramphenicol, streptomycin, sulfonamides, and tetracycline (ACSSuT resistance). The mechanism by which DT104 has accumulated resistance genes is of interest, since these genes interfere with treatment of DT104 infections and might be horizontally transferred to other bacteria, even to unrelated organisms. Previously, several laboratories have shown that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
1
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(156 citation statements)
references
References 17 publications
8
144
1
3
Order By: Relevance
“…On the other hand, chloramphenicol was banned from animal production in Brazil more than a decade ago. The occurrence of resistance against this antimicrobial could possibly be due to the emergence and spread of multi-drug resistant Salmonella isolates that harbour physically linked resistance to this drug, as previously reported (Briggs & Fratamico, 1999). Contrary to the increasing incidence of ciprofloxacin-resistant S. typhimurium reported in other countries (Angulo, Johnson, Tauxe, & Cohen, 2000;Threlfall, Ward, & Rowe, 1997), we did not find resistance to ciprofloxacin.…”
Section: Discussioncontrasting
confidence: 85%
“…On the other hand, chloramphenicol was banned from animal production in Brazil more than a decade ago. The occurrence of resistance against this antimicrobial could possibly be due to the emergence and spread of multi-drug resistant Salmonella isolates that harbour physically linked resistance to this drug, as previously reported (Briggs & Fratamico, 1999). Contrary to the increasing incidence of ciprofloxacin-resistant S. typhimurium reported in other countries (Angulo, Johnson, Tauxe, & Cohen, 2000;Threlfall, Ward, & Rowe, 1997), we did not find resistance to ciprofloxacin.…”
Section: Discussioncontrasting
confidence: 85%
“…They also found that a 1.0 Kb and 1.2 Kb integrons in S. Agona contained the aadA1 gene which confers resistance to streptomycin. The 13.078 bp of S. Typhimurium isolate contained four genes aadA2, sul1 tetA and bla CARB-2 which encode resistant to streptomycin, sulphonamides, tetraclycline and ampicillin, respectively (Briggs & Fratamico, 1999). Kwon et al (2002) in their work reported that the 1.0, 1.6, and 2.0 Kbp amplicons in S. Gallinarum contained one (addA1a), two (aadB-aadA1b) and three cassettes (dhfrXII-orf-aadA2) respectively, providing resistances against aminoglycosidase (aadA1a, aadA1b, aadB, and aadA2) and trimethoprim (dhfrXII).…”
Section: Results Inmentioning
confidence: 99%
“…It is currently unknown how or from which organism S. Typhimurium DT104 first acquired the SGI1. However, the floR gene (providing chloramphenicol/florfenicol resistance) is related (53% nucleotide identity) to the chloramphenicol resistance gene (cmlA) known to be located on a conjugative plasmid from Pseudomonas aeruginosa (Briggs & Fratamico, 1999). In addition, the tetracycline resistance region is highly related to genes found in a resistance plasmid from Vibrio anguillarum (Zhao & Aoki, 1992).…”
Section: Pathogenicity and Its Relation With Antimicrobial Resistancementioning
confidence: 99%
“…This class of antimicrobial agent has not been used in swine production for more than a decade (Gebreyes et al, 2004). The common occurrence of chloramphenicol resistance can largely be explained by the emergence and spread of MDR S. Typhimurium that harbor physically linked ACSSuT-resistance alleles, the most notable being members of S. Typhimurium DT104 (Briggs & Fratamico, 1999;Gebreyes & Altier, 2002;Threlfall, Ward, & Rowe, 1997).…”
Section: Other Serotypesmentioning
confidence: 99%
See 1 more Smart Citation